Strategi Biro Investigasi Praktik Korupsi Singapura sebagai Model Reformasi Kebijakan Antikorupsi - Hosy Muhammad Ali Imron; Arif Zainudin; Unggul Sugiarto (Universitas Wahid Hasyim Semarang, 2026)
Corruption is a significant issue that can hinder the achievement of good governance in various countries, including Indonesia. Although it has a Corruption Eradication Commission (KPK), the effectiveness of corruption eradication in Indonesia still faces numerous institutional, regulatory, and policy consistency challenges. Conversely, Singapore, through its Corrupt Practices Investigation Bureau (CPIB), has managed to maintain a consistently low level of corruption. This study aims to analyze the corruption eradication strategies implemented by the CPIB and identify opportunities for their adaptation in anti-corruption policy reform in Indonesia. The study used the Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines for selected scientific articles that met the inclusion criteria, supported by statistical data on the development of the CPIB's handling of corruption cases for the period 2021-2025. The analysis was conducted using thematic analysis with NVivo 12 software to identify themes, relationship patterns, and dominant factors influencing the effectiveness of corruption eradication. The research findings indicate that the success of the CPIB is influenced by the integration of institutional independence, a strong legal framework, political support, oversight mechanisms, the use of technology, anti-corruption education, public participation, and a consistent and sustainable culture of integrity. This research also demonstrates that the CPIB model cannot be directly implemented in Indonesia but requires adaptation through a selective policy adaptation approach, tailored to the characteristics of the national legal, political, and institutional systems. The research findings provide conceptual insights into the success factors of the CPIB anti-corruption model and serve as a reference for developing more effective and sustainable anti-corruption policy reforms in Indonesia.